Angioedema - Gina Lacuesta; Stephen D. Betschel; Ellie Tsai; Harold Kim (Allergy, Asthma & Clinical Immunology, 2024)
Abstract Angioedema can occur in the absence of urticaria and can be broadly divided into three main categories: mast cell-mediated (e.g., histamine), non-mast-cell-mediated (bradykinin-induced) and idiopathic angioedema. Non-mast-cell-mediated angioedema is largely driven by bradykinin. Bradykinin-induced angioedema can be hereditary, acquired or drug-induced, such as with angiotensin-converting enzyme (ACE) inhibitors. Although bradykinin-mediated angioedema can be self-limited, it can cause significant morbidity and laryngeal involvement may lead to fatal asphyxiation. The mainstays of management for angioedema are: (1) to avoid specific triggers (if possible and where known) and (2) treatment with medication (if indicated). For hereditary angioedema (HAE), there are specifically licensed treatments that can be used for the management of attacks, or for prophylaxis in order to prevent attacks. In this article, the authors will review the causes, diagnosis and management of angioedema.